Effects of Cynanchum bungei Decne Addition on the Physicochemical Properties and Antioxidant Activity of Rice Wine - Gonglin Cai; Hangmeng Dong; Shoulong Liu; Huabin Zhou; Hailong Yang (Fermentation, 2023)
Cynanchum bungei Decne is an agricultural crop with a high starch content and contains bioactive compounds with anti-tumor, anti-depressant, anti-oxidant, and other activities. In this work, three concentrations of C. bungei Decne, namely, 5%, 15%, and 25%, were added to media to brew C. bungei Decne rice wine. The basic physical and chemical properties, antioxidant activities, sensory characteristics, and volatile components of C. bungei Decne rice wine were determined. Furthermore, the effects of C. bungei Decne extract on the cell viability, alcohol dehydrogenase activity, and glucose absorption capacity of Saccharomyces cerevisiae were analyzed. The results showed that the main active compound contents and antioxidant activity of the rice wine were increased with the increase in the C. bungei Decne added. However, the vitality of Saccharomyces cerevisiae was inhibited by C. bungei Decne to some extent. Combined with a sensory evaluation, 15% C. bungei Decne was found to be the optimal additive concentration with which to brew C. bungei Decne rice wine. These data provide a theoretical basis for the development of C. bungei Decne rice wine.